A 40, 000-year record of aridity and dust activity at Lop Nur, Tarim Basin, northwestern China. (1st May 2019) - Liu, Jian; Wang, Rujian; Zhao, Yue; Yang, Yi
Abstract: The Taklamakan Desert is a major dust source area for northwestern China. The history of aridification and sandstorm activity of the desert is recorded in the lacustrine sediments of the Lop Nur paleolake, on the eastern margin of the desert. In this study, we used accelerator mass spectrometry 14 C dating, the ln (Al/Ca) ratio, and the grain size of the non-biogenic fraction of sediment core KY01 taken from the center of Lop Nur to produce a ∼40 kyr record of local climate change. During mid–late Marine Isotope Stage (MIS) 3, increases in the ln (Al/Ca) ratio, alluvial mud content, and atmospheric dust content, and a decrease in the dust storm content indicate an overall wet climate. During MIS 2, marked decreases in the ln (Al/Ca) ratio and alluvial mud content, especially during the Last Glacial Maximum and Heinrich event 1 cold interval, indicate lowered atmospheric temperatures, as also recorded in Greenland ice cores. During MIS 2, fluvial input to the site was reduced and almost ceased, suggesting extreme aridity at Lop Nur, very strong low-altitude winds, and frequent dust storms. During early MIS 1, the contribution of dust storms to the lake sediments fell gradually and was then relatively constant, even during the Younger Dryas cold interval. This result might be ascribed to the increased supply of meltwater from snow and ice to Lop Nur, representing a response to the rise in atmospheric temperatures during the deglacial, accompanied by strong high-level winds. During 9–7 kyr BP there was an increase in the input of sediment from sandstorms, and hence an increase in low-level wind strength, possibly relating to the 8.2 kyr BP cold event. From 7.0 to ∼1.5 kyr BP there was a decrease in sandstorm input and thus a gradual weakening of the strength of low-level winds. However, after ∼1.5 kyr BP the sandstorm input increased. Overall, we conclude that dust storm activity in the region of Lop Nur since 40 kyr BP has been controlled mainly by Northern Hemisphere cold events, with atmospheric dust providing a background sedimentary component that was dominant during warm intervals. Our findings contribute to an improved understanding of the dynamics of dust transport and to the history of dust activity and the lacustrine sedimentary record in northwestern China. Highlights: Low ln (Al/Ca) ratios during LGM, H1, and at ∼8.2 ka imply extremely arid conditions. Fluctuations in the grain-size end-members reveal global-scale warm and cold events. Low-altitude wind and sandstorms enhanced in LGM, H1, and cold intervals at 9–7 kyr. Greater dust supply from high-altitude winds during interglacial/interstadial periods. High alluvial mud in MIS 3, deglacial, and late Holocene implies paleolake expansion.